Deciphering condensed sequences: A case study from the Oxfordian (Upper Jurassic) Dhosa Oolite member of the Kachchh Basin, western India - Alberti, Matthias; Fürsich, Franz; Pandey, Dhirendra Kumar (Sedimentology, 2013)
In large parts of the Kachchh Basin, a Mesozoic rift basin situated in western India, the Oxfordian succession is characterized by strong condensation and several depositional gaps. The top layer of the Early to Middle Oxfordian Dhosa Oolite member, for which the term 'Dhosa Conglomerate Bed' is proposed, is an excellent marker horizon. Despite being mostly less than 1m thick, this unit can be followed for more than 100km throughout the Kachchh Mainland. A detailed sedimentological analysis has led to a complex model for its formation. Signs of subaerial weathering, including palaeokarst features, suggest at least two phases of emersion of the area. Metre-sized concretionary slabs floating in a fine-grained matrix, together with signs of synsedimentary tectonics, point to a highly active fault system causing recurrent earthquakes in the basin. The model takes into account information from outcrops outside the Kachchh Mainland and thereby considerably refines the current understanding of the basin history during the Late Jurassic. Large fault systems and possibly the so-called Median High uplift separated the basin into several sub-basins. The main reason for condensation in the Oxfordian succession is an inversion that affected large parts of the basin by cutting them off from the sediment supply. The Dhosa Conglomerate Bed is an excellent example, demonstrating the potential of condensed units in reconstructing depositional environments and events that took place during phases of non-deposition. Although condensed sequences occur frequently throughout the sedimentary record, they are particularly common around the Callovian to Oxfordian transition. A series of models has been proposed to explain these almost worldwide occurrences, ranging from eustatic sea-level highstands to glacial phases connected with regressions. The succession of the Kachchh Basin shows almost stable conditions across this boundary with only a slight fall in relative sea-level, reaching its minimum not before the late Early Oxfordian. © 2012 The Authors. Journal compilation © 2012 International Association of Sedimentologists.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.deciph
Keywords: Basin history; Condensation; Jurassic; Kachchh; Palaeogeography